Towards equitable genomics governance in Africa: Guiding principles from theories of global health governance and the African moral theory of Ubuntu - Munung, Nchangwi Syntia (Bioethics, 2022)
The post-genomics era promises a revolution characterized by precision medicine and the integration of genomics into almost every area of biomedical research. At the same time, there are concerns that if care is not taken, the genomics revolution may widen global inequities in science and health. In Africa, these concerns are primarily linked to the underrepresentation of African populations in genomics research, limited genomics research capacity in Africa and associated macro-level justice issues such as benefit sharing, inequitable international research collaborations, and the contribution of genomics to the health and research priorities of Africa. Addressing these concerns requires an in-depth reflection on how the ideals of global justice and equity may be advanced in genomics research. To contribute to the limited but growing scholarship on global genomics equity, especially in the African context, we performed a conceptual analysis of three accounts of justice and governance namely, Ubuntu, shared health governance and global governance of health, with the aim of identifying principles that could inform genomics governance in Africa. We used a convergence approach in the conceptual analysis, resulting in the identification of nine principles namely: solidarity, furthering the ideals of health justice, reciprocity, shared decision-making, shared resources, shared responsibility, mutual trust, transparency, and mutual collective accountability. Examples of how the principles may be applied are provided. We recommend that these principles should form the foundation of any mechanism that seeks to systematically advance justice, fairness and equity in genomics research in Africa and more broadly, global health and science equity.